RASIONALISASI DAN REALITAS BUDAYA JAWA TERHADAP MOTIF GURDA - Aan Sudarwanto (Brikolase, 2019)
The article that discusses the motive of the gurda aims to find out more clearly how the position and changes in the gurda motives in the perspective of Javanese society. In addition, it is also to find out the forms of the gurda motif and its application to Javanese culture from several perspectives, namely tradition, modern and postmodern.